The international Family Affluence Scale (FAS): Charting 25 years of indicator development, evidence produced, and policy impact on adolescent health inequalities - Currie, Candace; Alemán Díaz, Aixa Y; Bosáková, Lucia; de Looze, Margreet (SSM - population health, 2024)
In the absence of suitable indicators of adolescent socioeconomic status, the Family Affluence Scale (FAS) was first developed in Scotland 25 years ago. Since then, it has been adapted for use in the Health Behaviour in School-Aged Children (HBSC) Study to research inequalities in adolescent health in Europe and North America. FAS has also been used as an indicator of adolescent socioeconomic status in research studies outside of HBSC, worldwide. There has been a need for FAS to evolve and change its component items over time in order to take into account social and technological changes influencing the families of adolescents. This paper uniquely charts the development of FAS describing the methodological work carried out to validate the measure internationally and over time. It also presents an overview of the body of evidence on adolescent health inequalities produced over years from the HBSC Study and other research studies. Interviews conducted with policy stakeholders reveal that the evidence from FAS-related HBSC work has influenced their strategic work to raise awareness of inequalities and make the case for action to address these. Finally, the future of FAS is discussed with respect to its continual evolution in the context of technological, environmental and social change.
Keywords: Adolescent health; Family material deprivation; HBSC study; Policy impact; Socioeconomic inequalities; Global health indicators; Indicator development; Family affluence scale (FAS)